Project Creating Programming Capacities in Youth and Teachers in both Secondary and Higher Education and its challenge in the face of COVID-19 - Hernández-Ruiz, Irene (2021)
This work presents the university extension project of the Computer Science School of the National University titled Creating Programming Capacities in Young People and Teachers both in Secondary and Higher Education, its objectives, the methodology and the activities developed during the year 2020. It also describes the strategies implemented due to the challenges the project presented before the Covid-19.